PENGARUH TEMPERATUR TUANG , TEMPERATUR CETAKAN DAN TEKANAN TERHADAP STRUKTUR MIKRO, KEKERASAN METODE HIGH PRESSURE DIE CASTING (HPDC) PADUAN ALUMUNIUM-SILIKON - ade irvan tauvana (LPPM Politeknik Enjinering Indorama, 2020)
Metal Casting method High Pressure Die Casting (HPDC) is a method of casting by means of liquid metal into molds injection with velocity and pressure using HPDC machine. Molds are made from carbon steel used. Casting method is performed in the manufacture of Prints Disc Adapter and Stand Lamp with base material of Al-Si alloy 7.79% This study uses a pressure of 50 bar, 75 bar and 100 bar. Castings temperature variation is 7000C, 7500C, and 8000C while the mold temperature 2500C, 3000C, and 3500C. Temperature variation cast and mold temperature will affect the characteristics of the object casting product .. highest Hardness obtained at temperatures of 2500C molding, casting temperature of 7500C. with pressure of 75 bar is 79.94 BHN.